An Advanced Na–FeCl2 ZEBRA Battery for Stationary Energy Storage Application. Issue 12 (14th April 2015) - Li, Guosheng; Lu, Xiaochuan; Kim, Jin Y.; Viswanathan, Vilayanur V.; Meinhardt, Kerry D.; Engelhard, Mark H.; Sprenkle, Vincent L.
<x xml:space="preserve">Abstract</x> Sodium‐metal chloride batteries, ZEBRA, are considered one of the most important electrochemical devices for stationary energy storage applications because of its advantages of good cycle life, safety, and reliability. However, sodium–nickel chloride (Na–NiCl2) batteries, the most promising redox chemistry in ZEBRA batteries, still face great challenges for the practical application due to its inevitable feature of using Ni cathode (high materials cost). Here, a novel intermediate‐temperature sodium–iron chloride (Na–FeCl2) battery using a molten sodium anode and Fe cathode is proposed and demonstrated. The first use of unique sulfur‐based additives in Fe cathode enables Na–FeCl2 batteries can be assembled in the discharged state and operated at intermediate temperature (<200 °C). The results presented demonstrate that intermediate‐temperature Na–FeCl2 battery technology could be a propitious solution for ZEBRA battery technologies by replacing the traditional Na–NiCl2 chemistry.